Վարանդայի բանավոր մշակույթը Երվանդ Լալայանի և նրա թղթակից-բանահավաքների գրառումներում - Ս. Ա. Վարդանյան (ՀՀ ԳԱԱ հրատ.)
Сборник “Варанда” (материалы для будущих исследований) известного этнографа, фольклориста Е. Лалаяна является важным вкладом в историю армянской культуры. Вошедшие в сборник многожанровые фольклорные материалы по сей день не потеряли своей актуальности, являясь надежными первоисточниками по изучению фольклорной культуры упомянутого района. The volume “Varanda” (materials for further studies) of the famous ethnographer, folklorist Ye. Lalayan is an important contribution to the history of Armenian culture. The multi-genre folk materials, which are included in the volume, are applicable up to now. These are also reliable sources for comprehensive study of folk culture of above mentioned region.
Keywords: Geography; Anthropology; Recreation; Language and Literature; Folklore; Literature